Early Discharge from home health therapy services for people with Alzheimer's Disease and Related Dementias. (20th December 2022) - Knox, Sara; Downer, Brian; Haas, Allen; Ottenbacher, Kenneth J
Abstract: Background: People with Alzheimer's Disease and Related Dementias (ADRD) experience barriers to accessing care that they need, including home health therapy services (physical, occupational, and speech therapy). Clinicians report difficulty engaging patients with ADRD in therapy sessions, especially during the later stages of the disease. There is limited information about how the existing barriers and challenges impact an individual with ADRD's likelihood of being discharged from therapy services earlier than planned. The purpose of this study was to examine the relationship between early discharge from home health services and (a) dementia severity, (b) caregiver support, and (c) medication management. Method: This retrospective study derived data from 100% national Medicare Home Health data files from October 1, 2016 through September 30, 2017. A cohort of 111, 537 Medicare Fee‐for‐Service beneficiaries with ADRD was identified. A dementia severity categorization scale was used to classify individuals into one of six severity levels. Early discharge rates with associated 95% confidence intervals (CIs) were calculated for each patient characteristic. Multilevel logistic regression was used to estimate the relative risk (RR) of early discharge, by dementia severity level, caregiver support status, and level of medication assistance and adjusted for patient and clinical characteristics. Result: The overall early discharge rate was 13.3% (13.1, 13.5). Individuals who were in the most severe ADRD stage were the only group that had an increased likelihood of being discharged early (1.163; 1.003‐1.344) amongst people with ADRD. However, individuals who required assistance with medication demonstrated a decreased likelihood of early discharge at all levels (0.828; 0.741‐0.924) There was no significant difference in likelihood for early discharge across caregiver support levels. Conclusion: Despite a small increase in the most severe ADRD stage, the number of visits and the risk of early discharge was relatively consistent across severity stages. Further research is needed to assess whether the type and quality of services received varies across dementia stages. Individuals with ADRD who were independent with medication management had an increased likelihood of early discharge. Exploring this relationship in greater detail could inform clinician decisions about frequency and duration of care.